2020
DOI: 10.1002/nau.24489
|View full text |Cite
|
Sign up to set email alerts
|

Can abdominal hypropressive technique improve stress urinary incontinence? an assessor‐blinded randomized controlled trial

Abstract: Aim: To verify which one improves better stress urinary incontinence (SUI) symptoms: abdominal hypopressive technique (AHT) or pelvic floor muscle training (PFMT). Methods: Randomized controlled trial. Women with SUI who had not participated of physiotherapy program before were invited. The outcome measures were 7-day bladder diary, International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) and pelvic floor muscles (PFM) function measured by Modified Oxford grading System with vaginal palpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 22 publications
(66 reference statements)
1
19
0
6
Order By: Relevance
“…Furthermore, a pilot study done in 2012 showed an improvement in the vaginal resting pressure and MVC in athletic students who completed an eight-week program of PFM training [37]. Similarly, an RCT was conducted in 2020, dividing women with SUI that never had physiotherapy done before into those who underwent PFM training and those who had received the abdominal hypopressive technique [38]. Using questionnaire responses, researchers had shown that both the groups had an improvement in SUI; however, PFM training was found to be superior over abdominal hypopressive technique [38].…”
Section: Non-pharmacological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a pilot study done in 2012 showed an improvement in the vaginal resting pressure and MVC in athletic students who completed an eight-week program of PFM training [37]. Similarly, an RCT was conducted in 2020, dividing women with SUI that never had physiotherapy done before into those who underwent PFM training and those who had received the abdominal hypopressive technique [38]. Using questionnaire responses, researchers had shown that both the groups had an improvement in SUI; however, PFM training was found to be superior over abdominal hypopressive technique [38].…”
Section: Non-pharmacological Methodsmentioning
confidence: 99%
“…Similarly, an RCT was conducted in 2020, dividing women with SUI that never had physiotherapy done before into those who underwent PFM training and those who had received the abdominal hypopressive technique [38]. Using questionnaire responses, researchers had shown that both the groups had an improvement in SUI; however, PFM training was found to be superior over abdominal hypopressive technique [38]. The training consists typically of regular contraction and relaxation of the pelvic muscles, also known as Kegel exercises.…”
Section: Non-pharmacological Methodsmentioning
confidence: 99%
“…The main indications of HAG are the treatment of abdominal diastasis in the postpartum period, urinary incontinence and pelvic prolapse, as well as chronic LBP [ 17 ]. To date, the majority of studies have focused on assessing the effects of HAG on pelvic floor dysfunctions [ 20 , 21 , 22 ]. Nevertheless, very few studies have assessed the effects on other core muscle groups which form part of the core and which may help to stabilize the spine in a correct way [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas other tools such as manometry or dynamometry could be useful no superiority when assessing PFM has been reported 23 . Several authors, have compared PFM function and strength when performing HE and PFMT alone or in combination 19,24 . Jose‐Vaz et al 19 reported an improvement in UI symptoms, quality of life impact, and PFM function after 12 weeks of PFMT or HE with better scores in the PFMT group.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors, have compared PFM function and strength when performing HE and PFMT alone or in combination 19,24 . Jose‐Vaz et al 19 reported an improvement in UI symptoms, quality of life impact, and PFM function after 12 weeks of PFMT or HE with better scores in the PFMT group. On the other hand, there is evidence that both treatment models produce similar improvements in both baseline PFM strength and tone in women with PFD 24 .…”
Section: Discussionmentioning
confidence: 99%